Penguatan Literasi Sosial Mahasiswa PGSD dalam Pembelajaran Konsep Dasar IPS SD Berbasis Isu Aktual - Maria Magdalena Beatrice Sogen; Wasis Suprapto; Dodik Kariadi (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2006)
This study aims to analyze the strengthening of social literacy among PGSD students through issue-based learning in the Elementary Social Studies Basic Concepts course. The research employed a descriptive qualitative approach, with data collected through classroom observations, interviews with lecturers and students, and documentation of learning activities and student work. The findings reveal that, in the initial stage, students’ social literacy was predominantly descriptive, characterized by a superficial understanding of social issues and a limited ability to connect social studies concepts with contemporary social phenomena. The implementation of issue-based learning through stages of issue introduction, exploration and analysis using social studies concepts, critical discussion and social reflection, and synthesis of findings was shown to effectively enhance students’ social literacy. Students demonstrated improvements in analytical thinking toward social issues, the integration of social studies concepts with social realities, and the development of critical, reflective, and social empathy attitudes. The role of lecturers as facilitators and active student participation emerged as key factors in the success of the learning process. Nevertheless, the study also identified challenges related to the complexity of social issues, limitations in students’ analytical literacy, time constraints in lectures, and variations in students’ critical thinking abilities. These findings imply that issue-based social studies learning is a relevant pedagogical strategy for strengthening social literacy and for preparing prospective elementary school teachers with social awareness and critical thinking skills.